The influence of sleep deprivation on expression of apoptosis regulatory proteins p53, bcl-2 and bax following rat tongue carcinogenesis induced by 4-nitroquinoline 1-oxide - Juliana Noguti; Tathiana Aparecida Alvarenga; Mônica Levy Andersen; Sergio Tufik; Celina Tijuko Fujiyama Oshima; Daniel Araki Ribeiro (Wolters Kluwer Medknow Publications, 2013)
Background: The aim of this study was to evaluate whether paradoxical sleep deprivation could affects the mechanisms and pathways essentials for cancer cells in tongue cancer induced by 4-nitroquinole 1-oxide in Wistar rats. Materials and Methods: For this purpose, the animals were distributed into 4 groups of 5 animals each treated with 50 ppm 4 nitroquinoline 1 oxide (4 NQO) solution through their drinking water for 4 and 12 weeks. The animals were submitted to paradoxical sleep deprivation (PSD) for 72 h using the modified multiple platform method, which consisted of placing 5 mice in a cage (41 × 34 × 16 cm) containing 10 circular platforms (3.5 cm in diameter) with water 1 cm below the upper surface. The investigations were conducted using immunohistochemistry of p53, Bax and Bcl-2 proteins related to apoptosis and its pathways. Statistical analysis was performed by Kruskal-Wallis non-parametric test followed by the Dunn's test using SPSS software pack (version 1.0). P value < 0.05 was considered for statistic significance. Results: Although no histopathological abnormalities were induced in the epithelium after 4 weeks of carcinogen exposure in all groups, in 12 weeks were observed pre-neoplasic lesions. Data analysis revealed statistically significant differences ( P < 0.05) in 4 weeks group for p53 and for bcl-2 and for all immunomarkers after 12 weeks of 4NQO administration. Conclusion: Our results reveal that sleep deprivation exerted alterations in proteins associated with proliferation and apoptosis in carcinogenesis.